Extreme lateral interbody fusion (XLIF) approach for L5-S1: Preliminary experience - Xu, Junjie; Chen, Enliang; Wang, Le; Zou, Xiaobao; Deng, Chenfu; Chen, Junlin; Ma, Rencai; Ma, Xiangyang; Wu, Zenghui (Frontiers in Surgery, 2022)
Study Design Technical report. Objective Evaluate technical feasibility of extreme lateral interbody fusion (XLIF) at the L5-S1 level and provide an elaborate description of the surgical technique. Summary of Background Data With the development of surgical techniques, the indications for oblique lumbar interbody fusion (OLIF) surgery have been broadened to the L5/S1 segment. However, this technique also has limitations. Different from OLIF, the L5/S1 segment used to be considered the main contraindication for XLIF. To date, no authors have reported the application of XLIF at the L5/S1 level. Methods Only patients whose preoperative lumbar MRI showed the position of the psoas major muscles and blood vessels at the L5/S1 level were similar to those seen at supra-L5 levels were seleted. By folding the operating table, the iliac crest was moved downward to expose the L5/S1 intervertebral space during the operation. The remaining surgical procedures were consistent with routine XLIF surgery. Results 8 patients successfully underwent XLIF at the L5/S1 level. The L5/S1 disk spaces were always exposed sufficiently for disk preparation and cage insertion. The post operative radiographs showed a satisfactory L5/S1 reconstruction with good cage position. Only 1 patient (12.5%) felt thigh numbness, and the symptoms gradually resolved after surgery and were no longer present in a month. There were no cases of psoas hematoma, retrograde ejaculation or vascular injury. The postoperative VAS score showed that all the patients achieved satisfactory results. Conclusions XLIF at L5-S1 is feasible in strictly selected cases after thorough preoperative preparation and careful intraoperative procedures. However, we did not recommend XLIF as a routine surgical option at the L5/S1 level.